Structure–Activity Relationship Studies, SPR Affinity Characterization, and Conformational Analysis of Peptides That Mimic the HNK‐1 Carbohydrate Epitope. (3rd May 2017) - Ieronymaki, Matthaia; Nuti, Francesca; Brancaccio, Diego; Rossi, Giada; Real‐Fernández, Feliciana; Cao, Yihong; Monasson, Olivier; Larregola, Maud; Peroni, Elisa; Uziel, Jacques; Sabatino, Giuseppina; Novellino, Ettore; et al.
Abstract: The design of molecules that mimic biologically relevant glycans is a significant goal for understanding important biological processes and may lead to new therapeutic and diagnostic agents. In this study we focused our attention on the trisaccharide human natural killer cell‐1 (HNK‐1), considered the antigenic determinant of myelin‐associated glycoprotein and the target of clinically relevant auto‐antibodies in autoimmune neurological disorders such as IgM monoclonal gammopathy and demyelinating polyneuropathy. We describe a structure–activity relationship study based on surface plasmon resonance binding affinities aimed at the optimization of a peptide that mimics the HNK‐1 minimal epitope. We developed a cyclic heptapeptide that shows an affinity of 1.09×10 −7  m for a commercial anti‐HNK1 mouse monoclonal antibody. Detailed conformational analysis gave possible explanations for the good affinity displayed by this novel analogue, which was subsequently used as an immunological probe. However, preliminary screening indicates that patients′ sera do not specifically recognize this peptide, showing that murine monoclonal antibodies cannot be used as a guide to select immunological probes for the detection of clinically relevant human auto‐antibodies. Abstract : Cyclopeptides as sugar substitutes : Peptides can be instrumental to the development of immunological probes recognized by specific antibodies with improved affinity and specificity. We describe a structure–activity relationship study based on surface plasmon resonance binding affinities, aimed at the optimization of a peptide that mimics the HNK‐1 trisaccharide minimal epitope. We developed a cyclic heptapeptide that shows an affinity of 1.09×10 −7  m for a commercial anti‐HNK1 mouse monoclonal antibody.